2019
DOI: 10.1101/850636
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Testosterone improves muscle function of the extensor digitorum longus in rats with sepsis

Abstract: Among patients with Intensive care unit-acquired weakness (ICUAW), skeletal muscle strength often decreases significantly. This study aimed to explore the effects of testosterone propionate on skeletal muscle using rat model of sepsis. Male SD rats were randomly divided into experimental group, model control group, sham operation group and blank control group.Rats in experimental group were given testosterone propionate 2 times a week, 10 mg/kg for 3 weeks. Maximal contraction force, fatigue index and cross-se… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Longterm inhibition of mTORC1 signaling can cause myopathy [70]. A study showed that testosterone propionate promoted the phosphorylation of the mTOR signaling pathway, improving the strength, endurance, and volume of the skeletal muscle in septic rats [76]. Protein degradation in the skeletal muscle is similar to that of the mammalian cells and is under the control of two main proteolytic systems, including ubiquitin-proteasome and autophagy-lysosome [77].…”
Section: Discussionmentioning
confidence: 99%
“…Longterm inhibition of mTORC1 signaling can cause myopathy [70]. A study showed that testosterone propionate promoted the phosphorylation of the mTOR signaling pathway, improving the strength, endurance, and volume of the skeletal muscle in septic rats [76]. Protein degradation in the skeletal muscle is similar to that of the mammalian cells and is under the control of two main proteolytic systems, including ubiquitin-proteasome and autophagy-lysosome [77].…”
Section: Discussionmentioning
confidence: 99%
“…As testosterone signals via the mTOR pathway and androgen receptors leading to skeletal muscle hypertrophy [ 184 ], hypotestosteronemia may contribute to a net catabolic state resulting in ICUAW. In a septic rat model, short term treatment with testosterone propionate significantly improved maximum contractile force, and CSA of extensor digitorum longus muscle fibers without onset of testicular atrophy [ 185 ]. Importantly, testosterone treatment significantly increased protein levels of fast MyHC suggesting that testosterone may be a beneficial treatment to ameliorate ICUAW [ 185 ].…”
Section: Mechanisms and The Potential For Intervention During And mentioning
confidence: 99%
“…In a septic rat model, short term treatment with testosterone propionate significantly improved maximum contractile force, and CSA of extensor digitorum longus muscle fibers without onset of testicular atrophy [ 185 ]. Importantly, testosterone treatment significantly increased protein levels of fast MyHC suggesting that testosterone may be a beneficial treatment to ameliorate ICUAW [ 185 ]. Overall, hormone therapy for ICUAW has been met with encouraging pre-clinical data but limited clinical success.…”
Section: Mechanisms and The Potential For Intervention During And mentioning
confidence: 99%